Multiliteracies and technology enhanced education [ social practice and the global classroom - Cole, David R.; Pullen, Darren L. (Information Science Reference, 2010)
"This book will help readers understand the ways in which literacy is changing around the world, and to keep up to date with literacy research and reporting techniques"--Provided by publisher.